The Analysis of the Virtual Plataform "Reko" of the Universidad Tecnologica Metropolitana del Estado de Chile, from the Perspective of Experts and Professors - Moreno-Munoz, C (UNIV ESTATAL DISTANCIA, 2017)
The following article maintains the objective of analyzing the virtual platform REKO, of the Universidad Tecnologica Metropolitana de Santiago de Chile (UTEM), from the perspective of diverse actors under an analytical, interpretative, descriptive and qualitative point of view, applied to technical and pedagogical aspects. Two instruments of recollection were employed: firstly, an interview to two experts in design and virtual platform development and, in second place, a focal group constituted by eight professors of the School of Design of the UTEM. Considering the information obtained, through these two instruments, two general categories of analysis were obtained: one that corresponds to the technical and graphic design aspects of REKO, and another in relation to the pedagogical criteria that said platform must meet. The investigation proposes technical and pedagogical criteria of analysis that will allow the evaluation of this platform as a tool of support in superior education.